Research and production integration in the agricultural sector of the Bulgarian economy (1970–1990s) - Georgieva, Maria (Ukrainian Peasant, 2021)
Introduction. The degree of development and intensifi cation of agricultural production in Bulgaria in the 1970s and 1990s depended on its scientifi c substantiation, comprehensive implementation of the achievements of agricultural science in agricultural practice. In the second half of the twentieth century. Agrarian science became increasingly important, infl uencing the growth of Bulgaria’s economic development. The development of Bulgarian agricultural science has contributed to the establishment of international relations in the economic, scientifi c, technical and social spheres. In the second half of the twentieth century. In Bulgarian agriculture, the tendency to modernize agricultural production by achieving high and sustainable development of production, improving the quality of products by involving all factors, including the scientifi c achievements of agricultural science. Purpose. The aim of the study is to study the development of research and production integration in the agricultural sector of the Bulgarian economy in the 1970s and 1990s. Results. In the article for the fi rst time in domestic Bulgarian the question of infl uence of scientifi c and technical integration in agricultural production is considered. It was revealed that due to the introduction of the latest scientifi c theoretical knowledge in the production sphere a high level of development of the agricultural sphere was achieved, which increased the competitiveness, investment attractiveness and social orientation of the industry. Conclusion. As a result of the study, the author came to the following conclusions: - structural changes in agriculture, achieved in this period were carried out through the introduction of scientifi c advances in the agricultural production sphere, the use of the latest scientifi c technologies; - Measures taken to modernize the agricultural sector of the Bulgarian economy have contributed to increasing the level of productivity of the industry, improving sowing and planting material. - Priorities for the development of agricultural science to support indicators of agricultural production have been identifi ed